2018
DOI: 10.4110/in.2018.18.e19
|View full text |Cite
|
Sign up to set email alerts
|

L1 Recombinant Proteins of HPV Tested for Antibody Forming Using Sera of HPV Quadrivalent Vaccine

Abstract: Virus-like particles (VLPs) derived from human papillomavirus (HPV) L1 capsid proteins were used for HPV quadrivalent recombinant vaccine. The HPV quadrivalent vaccine is administrated in a 3-dose regimen of initial injection followed by subsequent doses at 2 and 6 months to prevent cervical cancer, vulvar, and vaginal cancers. The type 6, 11, 16, or 18 of HPV infection is associated with precancerous lesions and genital warts in adolescents and young women. The HPV vaccine is composed of viral L1 capsid prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The quadrivalent HPV vaccine, which leverages virus-like particles from the HPV L1 capsid protein, aims to replicate the HPV virus’s structure to stimulate a suitable immune response [23, 24]. Our findings show a homology between the HPV L1 capsid protein and key TED autoimmunity targets (IGF-1R and TSHR), suggesting potential autoimmune disease triggers from HPV L1 protein exposure or vaccination.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The quadrivalent HPV vaccine, which leverages virus-like particles from the HPV L1 capsid protein, aims to replicate the HPV virus’s structure to stimulate a suitable immune response [23, 24]. Our findings show a homology between the HPV L1 capsid protein and key TED autoimmunity targets (IGF-1R and TSHR), suggesting potential autoimmune disease triggers from HPV L1 protein exposure or vaccination.…”
Section: Discussionmentioning
confidence: 85%
“…However, in a separate study this group found no pattern of autoimmune diseases related to vaccine timing, dosage, or patient age, suggesting that the observed autoimmune thyroid cases might have pre-existed vaccination, as indicated by a non-elevated incidence rate ratio (IRR=0.72 [0.50-1.01]) upon detailed review [22]. The quadrivalent HPV vaccine, which leverages virus-like particles from the HPV L1 capsid protein, aims to replicate the HPV virus's structure to stimulate a suitable immune response [23,24]. Our findings show a homology between the HPV L1 capsid protein and key TED autoimmunity targets (IGF-1R and TSHR), suggesting potential autoimmune disease triggers from HPV L1 protein exposure or vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The gene could be amplified from keratynocyte cell line W12 (28), synthesized based on L1 gene downloaded from Genbank 11 , extracted from patients 30 , or ordered from ATTC company. 33 L1 gene used in this research is synthetic gene that codes a consensus L1 protein that represents the majority amino acid presented in different L1 HPV 16 proteins. Consensus sequence can accommodate the diversity of L1 HPV 16.…”
Section: Discussionmentioning
confidence: 99%
“…4 The main strategy to prevent HPV infection recommended by WHO is by vaccination. Nowadays there are three kinds of commercial prophylactic HPV vaccines, that are Gardsil, a quadrivalent vaccine containing HPV 6,11,16,18 antigens, Gardasil 9, a 9-valent vaccine containing HPV 6,11,16,18,31,33,45,52,58 antigens and a bivalent vaccine against HPV16 and 18 antigens. 3 The WHO recommends that the commercial HPV vaccine must cover at least two kinds of HPV subtypes, HPV 16 and HPV18 antigens.…”
mentioning
confidence: 99%
“…Since IL-32 transcripts were originally found in activated T-cells or NK cells it has important functions in pathogen infections-associated with Th1-mediated immune response (16). The roles of IL-32 against viral and intracellular bacterial infections have been studied by different research groups (12171819202122). IL-32 is involved in immune cell differentiation and proliferation during pathogen infections.…”
Section: Il-32 Variants In Different Diseasesmentioning
confidence: 99%